2018
DOI: 10.14742/ajet.3198
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of self-regulated learning in job characteristics and attitudes towards web-based continuing learning in the airlines workplace

Abstract: With the increasing importance of adult and continuing education, the present study aimed to examine the factors that influence continuing web-based learning at work. Three questionnaires were utilised to investigate the association of the job characteristics from Karasek et al.'s (1998) job demand-control-support model and the self-regulated learning with web-based continuing learning; exploratory factor analyses indicate their adequate reliability and validity. A sample of 203 employees of an airline compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…More precisely, the results suggest that, in particular, autonomy in methods, decision, and feedback from others related to selfefficacy, whereas autonomy in planning and task identity had no significant indirect effects on SRL strategies via self-efficacy. These results confirm previous studies (e.g., Joo and Park, 2010;Hans and Gupta, 2018), but they contradict other results (e.g., Simosi, 2012;Froehlich et al, 2014;Lin et al, 2018).…”
Section: Context Indirectly Enables Self-regulated Learning In Informsupporting
confidence: 86%
See 1 more Smart Citation
“…More precisely, the results suggest that, in particular, autonomy in methods, decision, and feedback from others related to selfefficacy, whereas autonomy in planning and task identity had no significant indirect effects on SRL strategies via self-efficacy. These results confirm previous studies (e.g., Joo and Park, 2010;Hans and Gupta, 2018), but they contradict other results (e.g., Simosi, 2012;Froehlich et al, 2014;Lin et al, 2018).…”
Section: Context Indirectly Enables Self-regulated Learning In Informsupporting
confidence: 86%
“…There is a lack of empirical research on SRL strategies ( Parker et al, 2017 ). Although some studies found that job characteristics can enhance SRL (see the review by Wielenga-Meijer et al, 2010 ; Gijbels et al, 2014 ; Noe et al, 2014 ; Lin et al, 2018 ), they do not investigate the relation to SRL in detail because they do not measure SRL according to current SRL model frameworks. Regarding motivation, a task accompanied by high autonomy and feedback leads to higher motivation ( Parker et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In East Asian countries, like China, are partial to this type of m‐learning owing to cultural influences and specific educational contexts. For instance, many Chinese learners use smartphones to watch, listen to, and memorize learning materials anytime and anywhere in preparation for highly competitive examinations (Lin, Liang, Tsai, & Hui, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In face-to-face education research, job match has a positive effect on individuals [28]. Furthermore, job characteristics have a significant relationship between attitudes towards distance education [29]. So, it is necessary to explore the relationship between job matching and distance education.…”
Section: Literature Reviewmentioning
confidence: 99%